Correlation Between Probiotic Use And Blood Pressure In Hypertensive Adults: A Cross-Sectional Study - Sultan, Dharma; Setyawan, Yuswanto (Poltekkes Kemenkes Bengkulu, 2025)
Hypertension remains a significant global health burden and is closely linked to cardiovascular morbidity. Emerging evidence suggests that gut microbiota plays an essential role in modulating blood pressure, particularly through the use of probiotics and prebiotics. This study investigated the relationship between the frequency of probiotic consumption and blood pressure control in patients with essential hypertension. A total of 100 hypertensive adults participated in this cross-sectional study, and data were collected through structured interviews, food frequency questionnaires, and blood pressure assessments. Statistical analyses included Chi-square and Spearman correlation tests. The results demonstrated a significant association between higher frequency of probiotic intake and better blood pressure control (p = 0.008), with a moderate negative correlation (r = –0.45) observed between intake duration and systolic blood pressure. Additionally, individuals who consumed both probiotics and prebiotic-rich foods exhibited enhanced blood pressure improvement. These findings support the potential of probiotic-prebiotic synergy in modulating gut microbiota to regulate blood pressure. The incorporation of prebiotics is essential, as they serve as substrates that stimulate the growth and activity of beneficial bacteria, thereby optimizing the efficacy of probiotic supplementation. The study highlights the practical implications of dietary interventions targeting the gut environment as a complementary strategy in hypertension management. Keywords: Hypertension, Probiotics, Prebiotics, Gut microbiota, Blood pressure